Detection of kidney complications relevant concentrations of ammonia gas using plasmonic biosensors : A review - Usman, Fahad; Kamarul Hawari, Ghazali; Razali, Muda; Dennis, John Ojur; Ibnaouf, Khalid Hassan; Aldaghri, Osamah A.; Alsadig, Ahmed; Nasrul Hadi, Johari; Rajan, Jose (MDPI, 2023)
Kidney-related health problems cause millions of deaths around the world annually. Fortunately, most kidney problems are curable if detected at the earliest stage. Continuous monitoring of ammonia from exhaled breath is considered as a replacement for the conventional blood-based monitoring of chronic kidney disease (CKD) and kidney failure owing to its cost effectiveness, non-invasiveness, excellent sensitivity, and capabilities for real-time measurement. The detection of ammonia for renal failure requires a biosensor with a detection limit of 1000 ppb (1 ppm). Among biosensors, plasmonic biosensors have attracted considerable research interest due to their potential for ultra-sensitivity, single particle/molecular level detection capability, multiplexing capability, photostability, real-time measurement, label-free measurement, room temperature operation, naked-eye readability, ease of miniaturization via simple sensor chip fabrication, and instrumentation, among other features. In this review, plasmonic sensors for the detection of ammonia gas relevant to kidney problems (LOD ≤ 1 ppm) are reviewed. In addition, the utilized strategies and surface functionalization for the plasmonic sensor are highlighted. Moreover, the main limitations of the reported sensors are stated for the benefit of future researchers. Finally, the challenges and prospects of plasmonic-based ammonia gas biosensors for potential application in the monitoring and screening of renal (kidney) failure, as well as the endpoint of the dialysis session, are stated.